The United States Holocaust Memorial Museum Encyclopedia of Camps and Ghettos, 1933-1945, Volume II Ghettos in German-Occupied Eastern Europe - Megargee, Geoffrey P.; Dean, Martin; Browning, Christopher R. (Indiana University Press, 2012)
This volume offers a comprehensive account of how the Nazis conducted the Holocaust throughout the scattered towns and villages of Poland and the Soviet Union. It covers more than 1,150 sites, including both open and closed ghettos. Regional essays outline the patterns of ghettoization in 19 German administrative regions. Each entry discusses key events in the history of the ghetto; living and working conditions; activities of the Jewish Councils; Jewish responses to persecution; demographic changes; and details of the ghetto's liquidation. Personal testimonies help convey the character of each ghetto, while source citations provide a guide to additional information. Documentation of hundreds of smaller sites-previously unknown or overlooked in the historiography of the Holocaust-make this an indispensable reference work on the destroyed Jewish communities of Eastern Europe.